2019
DOI: 10.17244/eku.395204
|View full text |Cite
|
Sign up to set email alerts
|

Fen Bilimleri Öğretmen Adaylarının Fen-Teknoloji-Mühendislik-Matematik (FeTeMM)’e Yönelik Özyeterlik Ölçeği: Türkçe’ye Uyarlama, Geçerlik ve Güvenirlik Çalışması

Abstract: Öz Makale Bilgisi Bu araştırmanın amacı, Friday Institute for Educational Innovation (2012a) tarafından geliştirilen Fen Bilimleri Öğretmenlerinin FeTeMM'e Yönelik Özyeterlik ve Tutumları Ölçeği'nin Fen Bilimleri öğretmen adaylarının özyeterlik düzeyini belirlemeye uygun olacak şekilde Türkçe'ye uyarlanmasıdır. Araştırmanın çalışma grubunu; çeşitli üniversitelerde Matematik ve Fen Bilimleri Eğitimi Bölümü, Fen Bilgisi Eğitimi Anabilim Dalı 3. ve 4. sınıf düzeyinde öğrenim gören 392 Fen Bilimleri öğretmen adayı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
3
0
2
Order By: Relevance
“…STEM attitudes of the pre-service teachers who will raise the generations of the future will enable them to make inferences about how they will promote the next generations. The positive attitudes of the pre-service teachers about STEM education show that students who display a positive perspective towards STEM education and have a tendency towards these fields can be a boost in the future (Gelen, Akçay, Tiryaki, & Benek, 2019). Thus, revealing the 21st-century skills competence perceptions of pre-service teachers and their STEM attitudes and STEM teaching intentions will render an insight into how they will shape the future.…”
Section: Introduce the Problemmentioning
confidence: 97%
“…STEM attitudes of the pre-service teachers who will raise the generations of the future will enable them to make inferences about how they will promote the next generations. The positive attitudes of the pre-service teachers about STEM education show that students who display a positive perspective towards STEM education and have a tendency towards these fields can be a boost in the future (Gelen, Akçay, Tiryaki, & Benek, 2019). Thus, revealing the 21st-century skills competence perceptions of pre-service teachers and their STEM attitudes and STEM teaching intentions will render an insight into how they will shape the future.…”
Section: Introduce the Problemmentioning
confidence: 97%
“…It is observed as a result of conducting a survey of the related national and international literature that many studies have been carried out on STEM education and selfefficacy for STEM practices (Abacı, 2020;Bakırcı & Kutlu, 2018;Boynukara, Deniz, Tüysüz, & 2020;Bölükbaşı & Görgülü-Arı, 2019;Brown, Concannon, Marx, Donaldson, & Black, 2016;Buechel, 2021;Cho & Lee, 2013;Çevik, Danıştay & Yağcı, 2017;Ertuğrul-Akyol, 2020;Faber, Alanda, Eric, & Wiebe, 2013;Gelen, Akçay, Tiryaki, & Benek, 2019;Hacıömeroğlu, 2020;Koçulu & Topçu, 2021;Önen-Öztürk, 2019;Öztürk, 2018;Öztürk, Yılmaz-Tüzün, & Çakır-Yıldırım, 2019;Saleh, 2016;Timur & İnançlı, 2018;Timur & Belek, 2020;Yaman et al, 2018). However, it is observed that international studies have mostly focused on students while national studies have generally focused on science, mathematics, information technology teachers as well as science teacher candidates.…”
Section: Related Literaturementioning
confidence: 99%
“…However, it is observed that international studies have mostly focused on students while national studies have generally focused on science, mathematics, information technology teachers as well as science teacher candidates. Whereas it is also understood that studies on self-efficacy for STEM practices are mostly scale development studies (Gelen, Akçay, Tiryaki, & Benek, 2019;Hacıömeroğlu, 2020;Luo, So, Li, & Yao, 2020;Yaman et al, 2018). It is also observed that there is a limited number of studies related to STEM education which have been conducted with primary school teacher candidates (Adams, Miller, Saul, & Pegg, 2014;Hacıömeroğlu & Bulut, 2016;Hacıömeroğlu, 2018;Kim & Bolger, 2017).…”
Section: Related Literaturementioning
confidence: 99%
“…Ulusal düzeyde FeTeMM eğitimi kapsamında öğretmen adaylarının görüşlerini ortaya koymak amacıyla farklı ölçme araçlarının geliştirildiği ve uyarlandığı görülmektedir. Araştırmalar incelendiğinde öğretmen adaylarının FeTeMM eğitimi kapsamında anlamsal algılarını (Kızılay, 2017), öğretim yönelimlerini (Hacıömeroğlu & Bulut, 2016), farkındalık düzeylerini (Buyruk & Korkmaz, 2016), tutumlarını (Derin, Aydın, & Kırkıç, 2017), öz yeterlik düzeylerini (Gelen, Akçay, Tiryaki, & Benek, 2019;Yaman, Özdemir, Akar, & Vural, 2018) incelemek amacıyla ölçme araçlarının geçerlik ve güvenirlik çalışmalarının yapıldığı görülmektedir. Kızılay (2017) (McKinney, Sexton, & Meyerson, 1999) düşük öz yeterliğe sahip öğretmenlerin ise görev odaklı endişelerinin yüksek olduğu (Ghaith & Shaaban, 1999) belirlenmiştir.…”
Section: öğRetmen Adayları Için Geçerlik Ve Güvenirlik çAlışması Yapıunclassified